Histone Acetylation, Not Stoichiometry, Regulates Linker Histone Binding in Saccharomyces cerevisiae. Issue 1 (26th July 2017) - Lawrence, Mackenzie B D; Coutin, Nicolas; Choi, Jennifer K; Martin, Benjamin J E; Irwin, Nicholas A T; Young, Barry; Loewen, Christopher; Howe, LeAnn J
Abstract: Linker histones play an important role in shaping chromatin structure, but the regulation of their interactions with chromatin is poorly understood... Linker histones play a fundamental role in shaping chromatin structure, but how their interaction with chromatin is regulated is not well understood. In this study, we used a combination of genetic and genomic approaches to explore the regulation of linker histone binding in the yeast, Saccharomyces cerevisiae . We found that increased expression of Hho1, the yeast linker histone, resulted in a severe growth defect, despite only subtle changes in chromatin structure. Further, this growth defect was rescued by mutations that increase histone acetylation. Consistent with this, genome-wide analysis of linker histone occupancy revealed an inverse correlation with histone tail acetylation in both yeast and mouse embryonic stem cells. Collectively, these results suggest that histone acetylation negatively regulates linker histone binding in S. cerevisiae and other organisms and provide important insight into how chromatin structure is regulated and maintained to both facilitate and repress transcription.